2017
DOI: 10.1590/s0004-2803.201700000-27
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Drinking a Probiotic Fermented Milk Beverage Containing Bifidobacterium Animalis on the Symptoms of Constipation

Abstract: -Background -Constipation is a chronic problem in many patients all over the world. Objective -To evaluate the effect of consumption of a probiotic fermented milk beverage containing Bifidobacterium animalis on the symptoms of constipation. Methods -This randomized, double-blind controlled trial included 49 female patients aged 20 to 50 years and diagnosed with constipation according to the ROME III criteria (Diagnostic Criteria for Functional Gastrointestinal Disorders) and the Bristol Stool Form Scale. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 15 publications
0
11
0
4
Order By: Relevance
“…Moreira et al found no difference in an RCT comparing an intervention group receiving a probiotic fermented milk beverage with a control group receiving non‐probiotic milk in 49 female patients with chronic constipation . Interestingly, the consumption of milk resulted in an improvement in constipation symptoms, regardless of the probiotic culture . In a well‐designed RCT, Spiller et al reported a positive effect of Saccharomyces cerevisiae in patients with IBS‐C .…”
Section: Resultsmentioning
confidence: 99%
“…Moreira et al found no difference in an RCT comparing an intervention group receiving a probiotic fermented milk beverage with a control group receiving non‐probiotic milk in 49 female patients with chronic constipation . Interestingly, the consumption of milk resulted in an improvement in constipation symptoms, regardless of the probiotic culture . In a well‐designed RCT, Spiller et al reported a positive effect of Saccharomyces cerevisiae in patients with IBS‐C .…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of participants who defecated at a consistent time each day decreased after kefir intervention and increased after milk intervention. Some other studies also found a beneficial effect of both kefir and milk on stool consistency or there were no differences compared to the control group (Moreira et al, 2017;Maki et al, 2018), while some studies have shown a beneficial effect of kefir or other probiotics on stool consistency, with the effect being significantly different from the control group (Lee et al, 2018;Yoon et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…The percentage of participants who defecated at a consistent time each day decreased after kefir intervention and increased after milk intervention. Some other studies also found a beneficial effect of both kefir and milk on stool consistency or there were no differences compared to the control group (Moreira et al, 2017;Maki et al, 2018), while some studies have shown a beneficial effect of kefir or other probiotics on stool consistency, with the effect being significantly different from the control group (Lee et al, 2018;Yoon et al, 2018).…”
Section: Discussionmentioning
confidence: 99%